Endo-/exo- and halogen-bonded complexes of conformationally rigid C-ethyl-2-bromoresorcinarene and aromatic N-oxides. Issue 30 (7th July 2017) - Puttreddy, Rakesh; Beyeh, Ngong Kodiah; Ras, Robin H. A.; Trant, John F.; Rissanen, Kari
Abstract : Unlike that of the conformationally flexible C -ethyl-2-methylresorcinarene the structurally more rigid C 4v cavity in C -ethyl-2-bromoresorcinarene prefers only small aromatic N -oxides stabilized through C–H⋯π interactions. Abstract : The host–guest complexes of conformationally rigid C -ethyl-2-bromoresorcinarene with aromatic N -oxides were studied using single crystal X-ray crystallography. Unlike that of the conformationally more flexible C -ethyl-2-methylresorcinarene, the C -ethyl-2-bromoresorcinarene cavity forms endo -complexes only with the small pyridine- N -oxides, such as pyridine N -oxide, 2-methyl-, 3-methyl- and 4-methylpyrdine N -oxide, and quinoline N -oxide. The larger 2, 4, 6-trimethylpyridine, 4-phenylpyridine and isoquinoline N -oxide, and 4, 4-bipyridine N, N ′-dioxide and 1, 3-bis(4-pyridyl)propane N, N ′-dioxide do not fit into the host cavity. Instead endo -acetone complexes are formed. Remarkably, differing from the anti – gauche endo -complex with C -ethyl-2-methylresorcinarene, the flexible 1, 3-bis(4-pyridyl)propane N, N ′-dioxide guest forms an anti – anti exo -complex with C -ethyl-2-bromoresorcinarene. The endo - and exo -complexes of C -ethyl-2-bromoresorcinarene and studied N -oxides manifest C–O⋯Br, C–H⋯π and C–Br⋯π interactions.